Evaluation Report - Holley, Paul (Youth for Youth Québec (Y4Y Québec), 2020)
The following evaluation report fulfills a key deliverable of a broader project funded by Canadian Heritage and titled Best Practices in Community Engagement for the English Speaking Youth Population in Quebec, which was implemented by Youth 4 Youth (Y4Y) Quebec from April 1, 2019 to March 31, 2020. The key objective of this project was to boost youth engagement and participation in political and community life in Quebec. Y4Y successfully accomplished this objective by engaging over 1,000 youth through a series of 30 community consultations, 12 focus groups, and a youth survey delivered on-line and in-person with 520 respondents. The focus of this report is on the key findings from the survey, which targeted Englishspeaking youth ages 16 to 30 from across the province and collected quantitative and qualitative information on youth media consumption and community engagement activities. A gender-based analysis of key survey findings was also conducted and is presented in this report along with a set of recommendations for community organizations serving Quebec’s English-speaking youth population.

Regional Priorities : QCGN Members 2018 - Quebec Community Groups Network (QCGN) (2018)
This document is a collaborative effort on the part of the regional member organization's of Quebec Community Groups Network to ensure regional priorities are at the fore of the Priority Setting Steering Committee discussions and to establish preferred and inclusive methods of consultation among regional member groups.

[Letter to Premier Couillard re: English Schools / Lettre au premier ministre Couillard concernant les écoles anglaises] - Quebec Community Groups Network (QCGN) (2015)

Assessing the English-speaking Community's Capacity to Access Arts, Culture, and Heritage in Nine Regions of Quebec : A Report on Phase One of the "Enhancing Access to Cultural Expression" Project (EACE) - Quebec Community Groups Network (QCGN); Palmer, Lise (2010)
In 2008, the Quebec Community Groups Network (QCGN) Board of Directors passed a formal resolution to prioritize the development of the Arts, Culture and Heritage sector. This area was prioritized by a majority of members in the Network and was supported by the Board. An Arts, Culture and Heritage working group was created to develop a policy framework in this area to streamline and guide the activities of the Network. The main partners in this endeavour were the English Language Arts Network (ELAN) represented by Guy Rodgers, the Quebec Anglophone Heritage Network (QAHN) represented by Kevin O'Donnell and Dwane Wilkin and the QCGN represented by Sylvia Martin-Laforge. Jane Needles also participated in the working group representing both the QCGN and ELAN. The policy framework, which was completed in November 2008, identified key areas of intervention over the next five years to support the dynamic growth and development of the cultural expression of English-speaking Quebec. The first was a project to access cultural expression through expanded partnerships. This current project “Enhancing Access to Cultural Expression” is a direct result of the prioritization of access to cultural expression. The other areas of priority included recognition and support through visibility - which is currently being addressed through the RAEV project being implemented by ELAN - and the creative economy - an issue yet to be addressed.